UNDERSTANDING AGING AND ITS IMPACTS: A QUALITATIVE STUDY OF THE PERSPECTIVES OF MIDDLE-AGED WOMEN IN MALAYSIA - Selvaraj, Shalini; Shanti C Sandaran (Malaysian Journal of Public Health Medicine, 2025)
The feminization of aging is a global phenomenon characterized by older women comprising much of the aging population. Given Malaysia’s designation as an aging nation since 2022, it is crucial to address the concept of the feminization of aging, which specifically relates to the unique experiences that women face as they grow older. As the middle-aged cohort represents the group closest to old age, their perception of aging profoundly influences their attitudes and behaviours as they approach the later stages of life. In this context, as middle-aged women navigate the transition from youth to old age, their perceptions and attitudes play a significant role in shaping their future well-being. The purpose of the study was to explore the perceptions of aging among middle-aged women, focusing specifically on both positive and negative aspects of aging. Through a qualitative analysis of interviews with 24 women in Malaysia, aged between 45 and 59, the study identified several key themes related to aging. Positive aspects of aging include increased knowledge, wisdom, and freedom, along with benefits and privileges for seniors. In contrast, the negative aspects revolve around health challenges such as increased health risks and emotional impacts. These perceptions are crucial for understanding how middle-aged women perceive and navigate their aging process. The findings provide insights into the need for aging research that considers both gender and cohort differences. The study highlights the need for targeted support programs that address the specific aging experiences of middle-aged women.